Cultivares de feijoeiro: efeito do solo, adubação foliar e competição com trapoeraba - Gomes, Lidiane dos Santos (2019)
The common bean (Phaseolus vulgaris L.) is one of the food consumed in Brazil, rich in vitamins, carbohydrates and minerals. A growing body of research that integrate from plant breeding and the management of fertilizer to increase nutrients in the edible parts, developing plants with higher levels of vitamins and micronutrients. The introduction of biofortified foods such as beans, complements human nutrition that suffers from malnutrition. Therefore, it is important to know how growing conditions influence the grain quality and the importance to obtain a food with higher nutritional value. Besides knowing how far the influence of weed affects the production and absorption of nutrients from the bean. The objective of this study was to analyze the agronomic and nutritional characteristics influenced by the interference of weed, effect of fertilization and soil in bean cultivars. Chlorophyll content, leaf number was assessed, stem diameter, number of pods per plant, harvest index per plant, dry matter of spiderwort, relationship grain and locus, average seed weight and iron and zinc in the leaves and analysis grains. The results of the study showed that competition with spiderwort affected some agronomic characteristics, due to competition for nutrients. The soil for cultivation also interfere with the production, eutrophic ground provided better results of cultivars. Fertilization did not affect the levels of iron and zinc in bean grains. The BRS Agreste, BRS Amethyst and BRS Style showed better results in most of the analyzed characteristics. Finally, it is concluded that the production of beans, needs a soil with good nutrition, a good organic matter content, management of fertilization and weed to increase production.